Preparation of boron-doped diamond microelectrodes to determine the distribution size of platinum nanoparticles using current transient method - Aliyah; Nurhidayat , Reza Rizqi; Afiten Rahmin Sanjaya; Rahmat Wibowo; Einaga, Yasuaki; Saepudin, Endang; Ivandini, Tribidasari Anggraningrum (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Boron-doped diamond (BDD) microelectrodes were prepared to investigate the correlation of hydrazine oxidation current responses with Pt nanoparticle (Pt NP) size distribution. The BDD film was grown on the surface of a tungsten needle with a diameter of 25 µm. An average particle size of around 5 µm BDD crystalline was successfully synthesized using a microwave plasma-assisted chemical vapor deposition technique. The Raman spectrum confirmed the presence of diamond formation as indicated by peaks corresponding to C-C sp3 bonds, while X-ray photoelectron spectroscopy spectrum showed the presence of C-H and C-OH bonds on the surface of the BDD microelectrode. Meanwhile the Pt nanoparticles was synthesized through reduction reaction of PtCl62- solution using NaBH4 with citric acid as the capping agent. Particles size between 4.46 to 4.78 nm were observed by using TEM measurements. The BDD microelectrodes were utilized to investigate the relationship between Pt nanoparticle size distribution and the current generated from the oxidation reaction of 15 mM hydrazine in a 50 mM phosphate buffer solution pH 7.4 in the presence of 1.0 mL nanoparticle solutions. A current range of 5 and 6 nA with a noise level of 0.15 nA was observed showing a good correlation with the particle sizes of Pt NPs. Comparison was also performed with the measurements using Au microelectrodes, indicated that the prepared BDD microelectrodes is promising for the measurements of nanoparticle sizes distribution, especially Pt NPs.